An analysis of the legislative protection of legal capacity for persons with mental and intellectual disabilities in Zimbabwe - Bhebhe, Vusumuzi (Midlands State University, 2017)
The Constitution of the Republic of Zimbabwe has an equality and non-discrimination clause that prescribes non-discrimination and proscribes any disability based discrimination. Zimbabwe, as a party to the Convention on the Rights of Persons with Disabilities, is obligated to construct its equality clause in line with the standards set out therein as the clause acquires a special meaning in relation to persons with mental and intellectual disabilities. The denial of legal capacity to persons with mental and intellectual disabilities under the prevailing legislative framework is at variance with Article 12 of the Convention on the Rights of Persons with Disabilities. There are multifarious statutes within Zimbabwe’s legislative framework which expressly and/or implicitly deny persons with mental and intellectual disabilities their legal standing and legal agency. Legal capacity is the conditio sine qua non for the realization of the rights of persons with mental and intellectual disabilities under any Constitution or human rights instrument. Accordingly, its denial renders any rights of persons with mental and intellectual disabilities nugatory. Zimbabwe is encouraged to emulate the legislative framework of the Republic of Ireland which has put into effect the presumption of legal capacity of persons with disabilities, a time and issue specific functional approach to legal capacity, moved towards the “will and preferences” paradigm and adopted supported decision making mechanisms for persons with mental and intellectual disabilities. It is recommended that Zimbabwe amends its Constitution to comprehensively capture its obligations under the Convention on the Rights of Persons with Disabilities, repeal its major pieces of legislation which deal with the legal capacity of persons with disabilities as well as amend a plethora of statutes which presume the legal incapacity of persons with mental and intellectual disabilities.